2001
DOI: 10.1128/jvi.75.8.3605-3612.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endogenous Avian Leukosis Viruses in Chicken Embryonic Fibroblast Substrates Used in Production of Measles and Mumps Vaccines

Abstract: Previous findings of low levels of reverse transcriptase (RT) activity in chick cell-derived measles and mumps vaccines showed this activity to be associated with virus particles containing RNA of both subgroup E endogenous avian leukosis viruses (ALV-E) and endogenous avian viruses (EAV). These particles originate from chicken embryonic fibroblast (CEF) substrates used for propagating vaccine strains. To better characterize vaccine-associated ALV-E, we examined the endogenous ALV proviruses (ev loci) present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The detection of ALV and EAV particles in live vaccines derived from chicken embryo fibroblast has been reported previously and investigated extensively (14,15,17). Seroconversion to ALV and EAV was not detected among a TOT refers to total nucleic acids directly extracted from the vaccine suspensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of ALV and EAV particles in live vaccines derived from chicken embryo fibroblast has been reported previously and investigated extensively (14,15,17). Seroconversion to ALV and EAV was not detected among a TOT refers to total nucleic acids directly extracted from the vaccine suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…Avian leukosis virus (ALV) and endogenous avian virus (AEV) have been reported in attenuated vaccines grown in chicken embryo fibroblasts (CEF), but extensive testing has also ruled out human infections (14,15). Vaccine-associated ALV and AEV are thought to originate from endogenous retroviruses in the chicken germ line (14,15,17).…”
mentioning
confidence: 99%
“…The ev-1 locus ubiquitously identified in CEF of White Leghorns expresses few or no particles, because the locus has a +1 frameshift mutation in the pol RT-b region, which resulted in a truncated RT-b subunit and integrase. 3,14,24 Recently, however, we isolated a strain of ALV (TymS_90) from layer chickens affected with fowl glioma in Japan. 10 This strain is different from FGV, and viral genome analysis suggests a recombinant ALV derived from ev-1 and other strains of avian leukemia and sarcoma viruses.…”
mentioning
confidence: 99%
“…The origin of RT activity has thus far been examined in measles vaccines produced in chicken embryonic fibroblasts (CEF). These studies have shown that this RT activity was associated with particles containing RNA from endogenous avian virus (EAV) and endogenous ALV (ALV-E) (17,28,30). These findings were consistent with current vaccine manufacturing regulations that require the elimination of exogenous retroviral infections from source chickens.…”
mentioning
confidence: 99%
“…The defective nature of ev-1 is a result of a ϩ1 frameshift mutation at nucleotide position 5026 within the pol region. This signature mutation truncates the ␣ subunit of RT (RT-␣) and inactivates integrase (17). ev-1 is ubiquitous in White Leghorns, and the other loci are less prevalent and vary in number depending on the chicken line (14).…”
mentioning
confidence: 99%